From Text to Animation: Adaptation of Bawang Putih Bawang Merah - Tengku Mohd Ali, Tengku Intan Marlina; Awang, Hashim; Mamat @ Mustaffa, Madiawati; Hashim, Nur Hamizah (Malay Literature, 2014)
The adaptation of literary texts into drama, film and animation is increasingly popular in today's era of advances in science and technology. Bawang Putih Bawang Merah (Garlic and Shallot) is one of the works which has been adapted into the form of film and animation. One of the animations adapted from text to film that received overwhelming response from the audience in 2001 was Putih directed by Rashid Sibir, produced by Fine Animation Sdn. Bhd. In animation, several changes are made, including changes to the title, characters and characters, setting and events to suit the target audience, and the times. In relation to this, the objective of this article is to analyse the adaptation from different Bawang Putih Bawang Merah texts into the animated form to ascertain the modifications made when certain works are converted into animation, and to investigate how far literary values are adapted into multimedia forms. This study will use the work of Rubaidin Siwar published by Dewan Bahasa dan Pustaka (1990) because it is a more complete text as compared to others. In discussing adaptations, Engelstad (2009) explains how there are four stages involved in the process of adaptation, the first being the narrative, the second the transformation of the verbal to visual, with the third stage being "enunciation", and the fourth being the comprehensive stage. All four stages are applied in the analysis of BPBM in its adaptation from text to animation. The adaptation process involved in converting the BPBM texts into the multimedia form retains the literary elements through the use of various story-telling techniques, to produce a captivating animated film. Although BPBM is a traditional Malay tale, the story is adapted with various interesting elements befitting the needs of today's generation. Keywords: animation, Bawang Putih Bawang Merah , adaptation, text, multimedia